2017
DOI: 10.1021/acs.joc.7b01096
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study of the BF3-Promoted Rearrangement of Oxiranyl N-Methyliminodiacetic Acid Boronates

Abstract: The mechanism of the rearrangement of oxiranyl N-methyliminodiacetyl (MIDA) boronates in dicholoromethane has been extensively investigated with density functional theory. Several reaction pathways were examined. Our results revealed that the most-favorable mechanisms for the BF-promoted rearrangement of 2-phenyl oxiranyl MIDA boronate (1) and 1-phenyl oxiranyl MIDA boronate (24) comprise two steps: ring opening of the epoxide to a carbocation intermediate followed by migration of a MIDA-boryl group (for the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 47 publications
1
12
0
Order By: Relevance
“…From Int4 , the bora‐Wagner–Meerwein rearrangement occurs via TS2 , with a barrier of 12.4 kcal mol −1 . Similarly to the studies of the groups of Yudin [9] and Pellegrinet [10] the migration occurs via a bora‐cyclopropane type structure ( TS2 ). Formation of a three‐membered ring‐shaped TS including electron deficient carbon centers represents a clear analogy to the Wagner–Meerwein rearrangement involving aryl/alkyl/H groups [19] .…”
Section: Figurementioning
confidence: 78%
See 1 more Smart Citation
“…From Int4 , the bora‐Wagner–Meerwein rearrangement occurs via TS2 , with a barrier of 12.4 kcal mol −1 . Similarly to the studies of the groups of Yudin [9] and Pellegrinet [10] the migration occurs via a bora‐cyclopropane type structure ( TS2 ). Formation of a three‐membered ring‐shaped TS including electron deficient carbon centers represents a clear analogy to the Wagner–Meerwein rearrangement involving aryl/alkyl/H groups [19] .…”
Section: Figurementioning
confidence: 78%
“…Mechanistic studies by Yudin and co‐workers [9] revealed that the high migration aptitude of MIDA boronate in this [1,2] process is due to the hemilabile bonding of nitrogen to boron in the Bmida group. Interestingly, this B‐N hemilability lends a migration aptitude to Bmida group, which is in the same magnitude as the ability of H/alkyl/aryl groups to undergo [1,2] migration to electron deficient carbon centers [10] . Electrophilic fluorination reactions are also known to proceed via carbocations or electron‐deficient carbon centers.…”
Section: Figurementioning
confidence: 99%
“…From Int4, the bora-Wagner-Meerwein rearrangement occurs via TS2, with a barrier of 12.4 kcal mol À1 . Similarly to the studies of the groups of Yudin [9] and Pellegrinet [10] the migration occurs via a bora-cyclopropane type structure (TS2). Formation of a three-membered ring-shaped TS including electron deficient carbon centers represents a clear analogy to the Wagner-Meerwein rearrangement involving aryl/alkyl/H groups.…”
Section: Methodsmentioning
confidence: 77%
“…On the other hand, stabilization of the positive charge by 2‐alkyl or 2‐aryl groups seems to be crucial for the rearrangement because the absence of a β‐substituent induces no rearrangement. A theoretical study suggested the formation of a carbocation by full ring‐opening from 2 in the case of 2‐aryl substituted substrates [8] . After that report, Li and Burke reported a stereoselective rearrangement of oxiranyl boronate derivatives having a chiral pinene‐derived iminodiacetic acid ligand [9] …”
Section: Ionic Reactionsmentioning
confidence: 99%
“…A theoretical study suggested the formation of a carbocation by full ring-opening from 2 in the case of 2-aryl substituted substrates. [8] After that report, Li and Burke reported a stereoselective rearrangement of oxiranyl boronate derivatives having a chiral pinene-derived iminodiacetic acid ligand. [9] In 2015, Yudin and co-workers reported rhodium-catalyzed intramolecular CÀ H amination of MIDA boryl sulfamate esters 4 (Scheme 2).…”
Section: Ionic Reactionsmentioning
confidence: 99%